Impact of interacting climate change factors on growth and ochratoxin A production by Aspergillus section Circumdati and Nigri species on coffee - Akbar, Asya; Medina, Angel; Magan, Naresh (Wageningen Academic Publishers, 2016)
The objectives of this study were to evaluate the effect of interacting climate change (CC) factors (water stress [water activity, aw; 0.99-0.90]); temperature [30, 35 °C]; and elevated CO2 [400 and 1000 ppm] on (1) lag phases prior to growth, (2) growth and (3) ochratoxin A (OTA) production by species of Aspergillus sections Circumdati and Nigri on coffee-based media and stored coffee beans. The lag phases, prior to growth, of all strains/species were slightly increased as aw, temperature and CO2 were modified. The interacting CC factors showed that most strains/species examined grew well at 30 °C and slightly less so at 35 °C except for Aspergillus niger (A 1911) which could tolerate the higher temperature. In addition, the interaction of elevated CO2 (1000 ppm) + temperature (35 °C) increased OTA production when compared with 30 °C but only for strains of Aspergillus westerdijkiae (B2), Aspergillus ochraceus (ITAL 14) and Aspergillus steynii (CBS 112814). Most of the strains had optimum growth at 0.95 aw at 35 °C, while at 30 °C the optimum was at 0.98 aw. On stored coffee beans there was only a significant stimulation of OTA production by A. westerdijkiae strains in elevated CO2 (1000) at 0.90 aw. These results suggest differential effects of CC factors on OTA production by species in the Sections Circumdati and Nigri in stored coffee and that for most species there is a reduction in toxin production.
Keywords: Aspergillus species; water activity; temperature; elevated CO2; growth; coffee; ochratoxin A